ETIKA GURU DALAM PERSPEKTIF HADIS - Daulae, Tatta Herawati (AIN Padangsidimpuan, 2013)
AbstractIslam says that teaching is a noble profession. Being a teacher is to teach, educate and train. Therefore, a teacher should have a science, academic and ethic. Here, prophetic tradition says that ikhlas, taqwa, science, patience and responsibility are necessary for a teacher to have.Finally, teacher’s ethic would take students’ sympathy, honour, and students’ easiness to study, obedience to god, wise, noble, success for any activity, and then he or she goes for beautiful long life.Key words: Ethic, Teacher, and Prophetic tradition